Controls of lateral and vertical variations in the geochemistry of the Hotazel Fe-Mn Formation at Nchwaning and Gloria mines, Kalahari Manganese Field, South Africa - Dorbor Jr., Stephen Baysah (Rhodes University, Faculty of Science, Department of Geology)
The Paleoproterozoic Kalahari manganese field (KMF) in the Northern Cape Province, South Africa, hosts a large resource of manganese ores that has been of great interest over many decades. The Kalahari Manganese deposit (KMD), which is the largest of five erosional relics of the Hotazel Formation in the KMF, hosts three beds of Mn ores with alternating layers of banded iron formation (BIF) and hematite lutite. These three rock types are all evaluated for their mineralogy and geochemistry in this study, with emphasis on lateral and vertical distributions across the Gloria and Nchwaning Mines in the northernmost KMF, an area of high-grade, hydrothermally altered Mn mineralisation. The Mn ores of the Hotazel formation are traditionally categorised into two types. The carbonate-rich low Mn grade (Mnâ‰¤40 wt. %) ores (Mamatwan-type) domninates the largest part of the KMD, while carbonate-free, high Mn grade (Mnâ‰¥ 45 wt.%) ore (Wessels-type) occurs in the northernmost KMD. The Wessels-type ores are considered as the hydrothermally altered product of Mamatwan-type ores, and as indicated above, are the focus of this study. Five drill cores containing Wessels-type ores from the Nchwaning and Gloria area of the northern KMD were analysed to help understand the petrographic and particularly the geochemical variations in the Hotazel Fe-Mn Formation, both laterally for a given Mn layer of the three, and vertically across Mn layers as captured in specific drillcores. Petrographic and whole-rock geochemical results obtained from the three rock types of the Hotazel Formation show variations in their mineralogical and geochemical compositions, especially in the high-grade Mn ores themselves. Most of the samples of the BIFs layers are dominated by hematite and chert occurring in banded fashion, which is typical of a normal carbonate-free altered BIF discussed in this thesis. The BIFs can also be locally enriched in hematite (ferruginised), occurring as massive hematite ores usually at the top of the stratigraphic profiles. The presence of aegirine-rich assemblages is also noted occurring in some of the BIF and hematite lutite sections immediately above and below the Mn ore beds. The high-grade Mn ore beds vary greatly in mineralogy and texture of the ores laterally and even within a single drill core. In an extreme case, a single drillcore sampled from the Gloria mine (GL57) contains high-grade Wessels-type ore in the upper Mn bed and low-grade, Mamatwan-type ore in the lower Mn layer. Geochemically, the Mn ore bodies also show substantial geochemical variability, although a net increase in the Mn grade downward is usually characterised by a corresponding depletion in mainly bulk Ca, Si and carbonate. However, the Fe content appears to be consistently higher in the upper ore bodies of the drillcores than the lower ones, and the increase in the concentration of the Fe-oxide expectedly causes a relative decrease in the bulk Mn-oxide concentration, usually expressed as an antithetic relationship between the two elements. In terms of trace element distributions, this appears to be more significant in the Mn ores than the other two rock types affected by the same alteration process, probably due to the presence of Mn phases such as hausmannite and braunite serving as good hosts to several trace elements. Cu, Zn, Pb and to a lesser extent Mo are trace metals that appear to show elevated concentration levels (net enrichments) in high-grade Mn ore by comparison to the presumed Mamatwan-type protolith. Ba is an additional element of clear enrichment, manifested mainly as the mineral barite. The Northern KMD has a complex post-depositional history, which includes the intrusion of NE-SW-trending dykes, formation of the Mapedi/Gamagara erosional unconformity, normal faulting associated with the Wessels event and major thrust faults in the western part of the northern KMD. These structural events all have the potential to have contributed to the alteration and subsequent enrichment of the Mn ores in the Nchwaning and Gloria area. As such, the mineralogical, textural, and geochemical variations observed here can tentatively be attributed to the different structural features in the northern KMD. Classic interpretations suggest that normal N-S-trending fault structures have acted as fluid conduits for hydrothermal fluids, which led to the metasomatic alteration of the Mn ore body laterally. Drill cores proximal to and evidently affected by fault-controlled alteration in the SE and SW-portions of the Nchwaning area, have comparable mineralogical and geochemical characteristics for both ore bodies (upper and lower) with subdued alteration effects from the unconformed contact above. Fluids associated with the Mapedi/Gamagara unconformity, would have percolated down-stratigraphy causing oxidative ferruginisation, which led to the formation of massive hematite ores in the top BIF layers and ferruginised Mn ores in the Mn ore beds. This alteration effect appears more prominent in a drill core from the northern part of the study area where the unconformity contact appears more proximal to the upper Mn bed. Drill cores located in the western part of the Nchwaning area seem to also capture evidence of fluid alteration with enrichment in Na recorded in the local abundance of the mineral aegirine. Finally, the dyke structures appear to have acted as impermeable fluid barriers to both lateral and possibly down-dip fluid-flow.
Keywords: Manganese ores Geology -- South Africa; Iron ores Geology -- South Africa; Geochemistry Geology -- South Africa; Kalahari manganese field; Banded iron formation; Hotazel mine